Analysis Of The Relationship Between Company Culture And Employee Achievement Motivation At PT. United Tractors Tbk - Nur Athirah Hadis; Nurfitriany Fakhri (PT. Padang Tekno Corp, 2024)
This research aims to determine the relationship between company culture and employee achievement motivation at PT United Tractors Tbk. This company is known for its good work culture, with the slogan